Stronnictwo regalistyczne w województwie kijowskim 1780-1782 - Filipczak, Witold (Przegląd Nauk Historycznych, 2009)
The article discusses the course of sejmik campaigns in the Kiev voivodeship from 1780 to 1782. It shows the activities of the royalist party led by Castellan of Kiev, Józef Stempkowski, who completely controlled the progress of deputational and pre-sejm sejmiks in Zhytomyr (Żytomierz was the city where sejmiks assembled in the Kiev voivodeship) in 1780. The journey to Ukraine made by King Stanisław August Poniatowski in 1781 was supposed to strengthen the position of local royalists. Yet the influence of the opposition became noticeable in 1782. Its leader Great Crown Hetman Franciszek Ksawery Branicki may have capitalized on his marriage (in 1781) to Aleksandra Engelhardt, a natural daughter of Empress Catherine II. The results of voting on particular issues during the Sejm of 1782 make it possible to discuss the political views of the Kiev envoys. Analyzing the course of the sejmiks from 1780 to 1782 and of the electoral sejmik in 1783, the author depicts the leading members of the royalist party in the Kiev voivodeship.